Finite element modeling for fatigue life prediction of RC beam strengthened with prestressed CFRP based on failure modes. (15th October 2019) - Guo, Xinyan; Wang, Yilin; Huang, Peiyan; Chen, Zhanbiao
Abstract: Compared to the technique with bonding carbon fiber reinforced polymer (CFRP) directly on reinforced concrete (RC) structures, an active strengthening technique with prestressed CFRP can make the stress distribution of RC structures more reasonable and improve the strengthening efficiency. Many experimental phenomena showed that, both two kinds of failure modes such as fatigue failure of main steel bars and debonding failure of CFRP-concrete interface, appeared in the CFRP strengthened specimens. However, to date there has not been an adequate analytical model considering both two kinds of failure modes to predict the servicing lives of RC structures strengthened with prestressed CFRP. In this paper, an analytical model comprehensively considering failure criterion of the main steel bars and the interface was established, and the failure mode of main steel bars or CFRP-concrete interface was predicted by finite element analysis (FEA). Based on the failure mode, servicing lives of RC beams strengthened with prestressed CFRP can be predicted by FEM. The results of finite element analyses were found to be in good agreement with experimental data, which were obtained by fatigue tests of RC beams strengthened with CFRP under four prestressing levels (0%, 10%, 15%, 22%).